2016
DOI: 10.1111/eci.12625
|View full text |Cite
|
Sign up to set email alerts
|

Increased iron levels and lipid peroxidation in a Mediterranean population of Spain

Abstract: In our general population, we have observed that higher circulating levels of iron, measured by serum ferritin and/or TS, increased lipid peroxidation (measured by oxLDL/LDL ratio).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 42 publications
1
13
0
Order By: Relevance
“…4a and b ). Elevated serum levels of iron not only may trigger free radical-mediated processes, but also activate immune system and induce inflammation as a form of an early protective response [ 35 ]. Available evidence suggests that some constituents of cranberry fruits may act as immunostimulants, mitigating the inflammation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…4a and b ). Elevated serum levels of iron not only may trigger free radical-mediated processes, but also activate immune system and induce inflammation as a form of an early protective response [ 35 ]. Available evidence suggests that some constituents of cranberry fruits may act as immunostimulants, mitigating the inflammation [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Serum ferritin is also recognized as an acute phase marker of inflammation. Some studies have explored whether elevated serum ferritin levels are associated with low-grade inflammation [32, 33], such as in chronic kidney disease [34], rheumatoid arthritis [35] and other autoimmune disorders [36]. These diseases exhibit low-grade inflammation and are mediated by oxidative stress, which is characterized by an imbalance between the generation of reactive oxygen species (ROS) and responses from the antioxidant defense system[37].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been observed that blood donors [32] and subjects undergoing phlebotomy [33] are more likely to prevent T2DM because of the corresponding decrease in B-IronS. It is speculated that oxidative stress [34,35] is the mechanism by which excess iron is associated with a higher incidence of T2DM. On the contrary, reduced B-IronS may entail a lower degree of oxidative stress, which in turn may decrease risk of T2DM.…”
Section: Discussionmentioning
confidence: 99%